Aboriginal art and Australian society : hope and disenchantment - Fisher, Laura, 1980- (Anthem studies in Australian literature and culture ;, 2016)
"'Hope and Disenchantment' is an investigation of the way the Aboriginal art phenomenon has been entangled with Australian society's negotiation of Indigenous people's status within the nation over the last century. Through critical reflection on Aboriginal art's idiosyncrasies as a fine arts movement, its vexed relationship with money, and its mediation of the politics of identity and recognition, this study illuminates the mutability of Aboriginal art's meanings in different settings. It reveals that this mutability is a consequence of the fact that a range of governmental, activist and civil society projects have appropriated the art's vitality and metonymic power in national public culture, and that Aboriginal art is as much a phenomenon of visual and commercial culture as it is an art movement. Throughout these examinations, Fisher traces the utopian and dystopian currents of thought that have crystallised around the Aboriginal art movement and which manifest the ethical conundrums that underpin the settler state condition"--